Peningkatan Hasil Belajar Akuntansi dengan Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Pada Siswa Kelas XII IPS 1 SMA Negeri 1 Kerinci - Sunardi Latif (Universitas Batanghari Jambi, 2020)
This study was classroom action research. It was conducted due to the students’ difficulties related to accountancy materials and questions. It could be seen that the student’s learning activeness and achievement were still low during the learning and teaching process. Therefore, the researcher tried to find solution to improve the student’s learning activeness and achievement by applying Think Pair Share (TPS) learning model. The research participants were the students of grade XII IPS 1 SMAN 1 Kerinci. The significance of the research was to enable the students to answer the questions and exercises in accountance material as well as improve their activeness during the learning and teaching process. The researcher was helped by a collaborator who was also the teacher of the same subject to observe the activities. The research was conducted in two cycles in which each of them had four stages namely (a) planning (b) action (c) observation (d) reflection. The data analysis result showed that the student’s learning activeness and achievement improved significantly after Think Pair Share learning model was implemented. In cycle I, there were 8 (40%) students who were active in apperception, 9 (45%) active students during the learning process, then 9 students (45%) who were actively involved in discussion, and 9 (45%) students who got achieved level in learning . In cycle II, the student’s activeness became higher to 75% (15 students) in apperception, 80% (16 students) during the learning process, 80% (16 students) during the discussion, and 85% (17 students) who got achieved criteria in learning. It could be concluded that the implementation of Think Pair Share learning model improved the student’s learning activeness and achievement on accountace subject at grade XII IPS 1 SMAN 1 Kerinci. Therefore, it was suggested for teachers to apply Think Pair Share (TPS) Learning model as one of solution towards the student’s problem in class especially in Accountancy subject.